The 'double transition': a novel electrocardiogram sign to discriminate posteroseptal accessory pathways ablated from the right endocardium from those requiring a left-sided or epicardial coronary venous approach. Issue 11 (27th September 2020) - Pascale, Patrizio; Hunziker, Samuel; Denis, Arnaud; Gómez Flores, Jorge Rafael; Roten, Laurent; Shah, Ashok J; Scherr, Daniel; Komatsu, Yuki; Ramoul, Khaled; Daly, Matthew; LeBloa, Mathieu; Pruvot, Etienne; et al.
Abstract: Aims: The precise localization of manifest posteroseptal accessory pathways (APs) often poses diagnostic challenges considering that a small area may encompass AP that may be ablated from the right or left endocardium, or epicardially within the coronary sinus (CS). We sought to explore whether the QRS transition pattern in the precordial lead may help to discriminate the necessary ablation approach. Methods and results: Consecutive patients who underwent a successful ablation of a single manifest AP over a 5-year period were included. Standard 12-lead electrocardiograms were reviewed. A total of 273 patients were identified. Mean age was 31 ± 15 years and 62% were male. Of the 110 identified posteroseptal AP, 64 were ablated from the right endocardium, 33 from the left endocardium, and 13 inside the CS. While a normal precordial QRS transition was most often observed, a subset of 33 patients presented an atypical 'double transition' pattern which specifically identified right endocardial AP. The combination of a q wave in V1 with a proportion of the positive QRS component in V1 < V2 > V3, predicted a right endocardial AP with a 100% specificity. In case of a positive QRS sum in V2, this 'double transition' pattern predicted a posteroseptal right endocardial AP with 99.5% specificity and 44% sensitivity. The positive predictive value was 97%. The only false positive was a midseptal AP. In the case of a negative or isoelectric QRS sum in V2, APs were located more laterally on the tricuspid annulus. Conclusion: The combination of a q wave in V1 with a double QRS transition pattern in the precordial leads is highly specific of a right endocardial AP and rules out the need for CS or left-sided mapping.